Efektivitas Ekstrak Daun Sidaguri (Sida Rhombifoli L) Terhadap Kematian Larva Aedes aegypti - Rezki Rahmatullah; Andi Susilawaty; Habibi Habibi; Syahrul Basri (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2020)
Aedes aegypti is a vector that transmits dengue virus and causes Dengue Haemorrhagic Fever (DHF). The increasing number of DHF case has caused major fatality annually. The use of chemical larvicide is not entirely environmentally friendly. On the contrary, plant based larvicide has been proven to be effective in controlling larvae while subduing the negative impacts of larvicide use to environment. This research investigates the efficacy of arrowleaf sida extract (Sida rhombifolia L) as a larvicide in killing Aedes aegyti larvae. It uses quantitative approach with true experiment method in testing the hypothesis. The research samples consist of 500 larvae which are divided into four groups with different treatments (0.25%, 0.50%, 0.75% dan 1%) and four reapplications within a time span of 1440 minutes. The findings show that the average percentage of Aedes aegypti larvae death with 0.25% concentration is 6.25%, 0,50% concentration is 12,25%, 0,75% concentration is 15,25%, and 1% concentration is 18,25%. The result of ANOVA test is p-value = 0.001 (p= <0.05) which further indicates the correlation between the death of larvae and arrowleaf sida extract intervention. This research hopes that the research findings can contribute to the success of Aedes aegypti larvae eradication program.Keywords: Aedes aegypti larvae, arrowleaf sida extract, the death of larvae